STRUKTUR ORGANISASI SEKOLAH DAN IMPLIKASINYATERHADAP EFEKTIVITAS PENGAMBILAN KEPUTUSANMANAJERIAL - Manarur Mizal; Zaid Halim Nur Rahmat; Muhammad Kholil Al Ghofar (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The organizational structure of a school is a formal framework that regulates the division of tasks, authority, and responsibilities among elements within the institution. This structure significantly influences how managerial decision-making is carried out by principals, vice principals, teachers, and administrative staff. This study aims to analyze the relationship between school organizational structure and the effectiveness of managerial decision-making. The method used is a literature study by reviewing relevant references in educational management, organizational structure, and decision-making practices in schools. The results show that a clear, flexible, and participatory organizational structure can improve decision-making effectiveness by ensuring more efficient communication, better coordination, and well-distributed responsibilities. Conversely, rigid and bureaucratic structures may slow down the process and reduce the school’s adaptability to change. The findings highlight the importance of principals in designing an organizational structure that supports collaboration, transparency, and efficiency in managerial decision-making.